The facies analysis of the Cenomanian –Turonian succession of Surdash –Shaqlawa area, NE. Iraq - S.Al-Sheikhly, Saad; Y.Tamar-Agha, Mazin; M. Mahd, Maher (Iraqi Journal of Science, 2023)
Three formations were studied from seven outcrops extend from Surdash toShaqlawa (Cenomanian – Santonian), they comprise Dokan, Gulneri and KometanFormations. Four microfacies and eight submicrfacies are identified depending onthis microfacies, we determine the depositional environments. Dokan Formation isdeposited in open-marine deep shelf environment; it could be deposited at deepershelf to slope and basinal settings. While Gulneri Formation deposited in open seashelf, as well as at outer shelf settings, the sediments consist of organic–carbon richblack shale and consider a record of the ocean anoxic event 2, Kometan Formationrepresent pelagic sediments characterize the deep-marine basins in open marine.